Outcomes of Lung Transplantation for Cystic Fibrosis in the Setting of Extensively Drug-Resistant Organisms. (September 2019) - Winstead, Ryan J.; Waldman, Georgina; Autry, Elizabeth B.; Evans, Rickey A.; Schadler, Aric; Kays, Lindsey; Baz, Maher; Anstead, Michael I.; Shafii, Alexis; Goetz, Megan E.
Introduction: Since the largest study on extensively drug-resistant organisms and lung transplantation in patients with cystic fibrosis, there have been innovations and advancements in the treatment of Pseudomonas aeruginosa . Research Question: What differences exist for patients with cystic fibrosis with a history of extensively drug-resistant infections who undergo lung transplantation despite treatment advances with antimicrobial therapy? Study Design: Two-center, retrospective, cohort study conducted in 44 patients with cystic fibrosis chronically infected with extensively drug-resistant organisms who received a lung transplant from January 2008 through August 2016. Patients in the resistant cohort were chronically infected with pan-resistant P aeruginosa, polymyxin-sensitive only, or sensitive to 2 antibiotic classes (polymyxin plus one other); remaining patients with more susceptible P aeruginosa or no P aeruginosa remained in the control cohort. The primary outcome is a composite of patient survival, retransplantation, chronic lung allograft dysfunction, and acute rejection 12 months posttransplant. Categorical variables were analyzed using χ 2 testing. The independent samples t test was utilized for continuous variables. Results: There was no difference in the primary outcome (40% vs 37%, P = .831). Differences between patient survival (84% vs 95%, P = .487), the incidence of acute rejection (20% vs 33%, P = .323), and the incidence of chronic lung allograft rejection (12% vs 5%, P = .441) were not different between groups. Discussion: Recipients chronically infected with an extensively resistant P aeruginosa had similar outcomes compared to those infected with more sensitive organisms.